2005
DOI: 10.1038/sj.emboj.7600562
|View full text |Cite
|
Sign up to set email alerts
|

Lip1p: a novel subunit of acyl-CoA ceramide synthase

Abstract: Ceramide plays a crucial role as a basic building block of sphingolipids, but also as a signalling molecule mediating the fate of the cell. Although Lac1p and Lag1p have been shown recently to be involved in acyl-CoA-dependent ceramide synthesis, ceramide synthase is still poorly characterized. In this study, we expressed tagged versions of Lac1p and Lag1p and purified them to near homogeneity. They copurified with ceramide synthase activity, giving unequivocal evidence that they are subunits of the enzyme. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
124
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(130 citation statements)
references
References 60 publications
(69 reference statements)
6
124
0
Order By: Relevance
“…The mammalian homologues of yeast LAG1 were later identified in human, Caenorhabditis elegans (19), and mouse (17), and recent independent studies have shown specific functions of mouse LASS1, LASS5, and LASS6 in the specific generation of C 18 -, C 16 -and C 14 /C 16 -ceramides, respectively (17,30,31). Importantly, although the yeast LAG1 requires LAC1 and Lip1 for the generation of ceramide (34), mouse LASS5 was shown to be a bona fide (dihydro)ceramide synthase without any detectable requirement for any associated proteins for its enzyme activity (31), suggesting distinct regulatory mechanisms for the ceramide synthase function of LAG1-related proteins in yeast versus mammalian cells. In addition, the role for LASS1 in the regulation of growth and apoptosis of neuronal ceroid lipofuscinosis, a hereditary childhood neurologic disorder, has been recently shown, confirming the distinct and important roles of LAG1-generated ceramide in various biological disorders (23).…”
Section: Discussionmentioning
confidence: 99%
“…The mammalian homologues of yeast LAG1 were later identified in human, Caenorhabditis elegans (19), and mouse (17), and recent independent studies have shown specific functions of mouse LASS1, LASS5, and LASS6 in the specific generation of C 18 -, C 16 -and C 14 /C 16 -ceramides, respectively (17,30,31). Importantly, although the yeast LAG1 requires LAC1 and Lip1 for the generation of ceramide (34), mouse LASS5 was shown to be a bona fide (dihydro)ceramide synthase without any detectable requirement for any associated proteins for its enzyme activity (31), suggesting distinct regulatory mechanisms for the ceramide synthase function of LAG1-related proteins in yeast versus mammalian cells. In addition, the role for LASS1 in the regulation of growth and apoptosis of neuronal ceroid lipofuscinosis, a hereditary childhood neurologic disorder, has been recently shown, confirming the distinct and important roles of LAG1-generated ceramide in various biological disorders (23).…”
Section: Discussionmentioning
confidence: 99%
“…De novo ceramide synthesis begins in the endoplasmic reticulum with the serine palmitoyltransferase-catalyzed condensation of serine and palmitoyl-CoA and a subsequent series of reactions produce ceramide on the cytosolic side of the ER ( Mandon et al, 1992;Hirschberg et al, 1993;Michael and Van Echten Deckert G, 1997;Cuvillier et al, 1996). Lip 1p, a novel subunit of the enzyme ceramide synthase, the active form of which has been recently purified from yeast, is a singlespan ER membrane protein required for ceramide synthase activity (Vallee and Riezman, 2005).…”
Section: Ceramide Metabolismmentioning
confidence: 99%
“…part to avoid issues related to the reported hetero-oligomerization of these subunits (16). However, because the alanine mutants are lethal in the context of a lac1⌬ lag1⌬ strain, we used a tetracycline-repressible (TetR) system (32), wherein a repressible version of WT Lac1 or Lag1 was paired with constitutively expressed, GFP-tagged versions of the other subunit.…”
Section: Cka2 Regulates Sphingolipid Biosynthesis At Thementioning
confidence: 99%
“…Specifically, in yeast, two functionally redundant isoforms exist, encoded by the genes LAC1 and LAG1, whereas at least six different isoforms exist in mammalian cells (CerS1 to -6) (15). In addition, yeast have an essential regulatory subunit encoded by LIP1 that is required for CerS activity both in vitro and in vivo (16). The early steps of the pathway, including formation of ceramides by CerS, take place within the endoplasmic reticulum (ER) membrane (17).…”
mentioning
confidence: 99%